Effects of zumba fitness program on body composition of women - Adriana Ljubojević; Vladimir Jakovljević; Milijana Popržen (University of Banja Luka, Faculty of physical education and sport, 2014)
The aim of this research was to determine the effects of zumba fitness program on changes of women body composition. 12 women aged 25-35 participated in the conducted research. The zumba fitness program was estimated after eight weeks of exercise, total of 24 training sessions. Body weight, fat percentage, fat mass, fat free mass and total body water were measured at the beginning and at the end of the research. The effects of fat-free training model were analyzed by using Paired sample T test. The obtained result showed that zumba fitness program achieved statistically significant improvement in total body weight loss (p=.019), fat percentage (p=.012) and fat free (p=.000). Although the value of fat free mass (0.22 kg) and the total amount of body water (0.15 kg) recorded increase after completed program, they were not statistically significant. The study results clearly indicated that the zumba fitness exercise can be used as effective group fitness exercise for the change in body composition of women.